Economic Contributions from Conserved Forests: Four Case Studies of the USDA Forest Service Forest Legacy Program - Helena Murray; Paul Catanzaro; Marla Markowski-Lindsay; Brett J Butler; Henry Eichman (Forest Science, 2021)
Privately-owned forests provide important environmental, economic, and cultural benefits to the general public. Resulting impacts from landownership changes and conversion of working forests to other land uses threaten these benefits. The USDA Forest Service Forest Legacy Program (FLP) permanently protects threatened private forests that are of environmental, cultural, and economic importance to the greater public while keeping land ownership and forest management at the private or local level. FLP provides grants to state agencies to purchase conservation easements on private forestlands or, less frequently, acquisition by public agencies. We employed IMPLAN’s input-output model of the 2016 economy to estimate how land protected by FLP in four regions of the United States contributes to the economy. FLP land adds tens of millions of dollars of value annually and supports thousands of jobs in the four study areas and, due to the permanent protection of these lands, they will continue to do so in perpetuity. Nonfederal partners contributed 34%–60% of total project costs, highlighting the importance of land conservation to multiple stakeholders and the ability to leverage federal resources. The permanent nature of FLP protection provides long-term security for the economic and cultural benefits these lands provide.